Establishment of method for identification of water quality in fire-tube boiler - a case study for UTHM Biodiesel Plant's Boiler - Nik Muhamad Kamal, Nik Muhammad Akif; Nasir, Nurul Fitriah; Abdul Patar, Muhammad Affifudin; Sies, Mohamad Farid; Hariri, Azian; Mat Isa, Norasikin; Nordin, Normayati; Wan Salim, Wan Saiful Islam (International Journal of Integrated Engineering, 2019)
Water treatment process for a boiler is essential to ensure the boiler operates at an optimum condition. Accordingly, the present study aimed to introduce a water quality assurance method for a boiler at UTHM biodiesel plant. The water quality is investigated by experimental study, which includes the monitoring of total dissolved solids, potential of Hydrogen (pH), sulphate, iron and chloride content, total hardness, and alkalinity. The water sampling was conducted at three different points. Subsequently, for the purpose of water quality assurance, the amount and type of chemical needed for a boiler to maintain a substantial value of water treatment were also been determined. The results obtained in this study has revealed that most of the parameters investigated are within the allowable limits. Further work needs to be done to establish whether the steam produced by the boiler can be influenced by the boiler water quality.